Enhancing team success in the neonatal intensive care unit: challenges and opportunities for fluid teams - Bell, Elizabeth A.; Rufrano, Gabrielle A.; Traylor, Allison M.; Ohning, Bryan L.; Salas, Eduardo (Frontiers in Psychology, 2023)
Fluid teams, characterized by frequent changes in team membership, are vital in the neonatal intensive care unit (NICU) due to high patient acuity and the need for a wide range of specialized providers. However, many challenges can hinder effective teamwork in this setting. This article reviews the challenges related to fluid teamwork in the NICU and discusses recommendations from team science to address each challenge. Drawing from the current literature, this paper outlines three challenges that can hinder fluid teamwork in the NICU: incorporating patient families, managing hierarchy among team members, and facilitating effective patient handoffs. The review concludes with recommendations for managing NICU teamwork differently using strategies from team science.